Determination of phenylbutazone, sulfamethazine, carbendazim and linuron using a novel pine bark biosorbent for solid-phase extraction (SPE) with high-performance liquid chromatography (HPLC). Issue 5 (3rd September 2022) - Khazri, Hassen; Boczkaj, Grzegorz; Ghorbel-Abid, Ibtissem; Trabelsi-Ayadi, Malika
Abstract: The paper presents a novel pine bark based biosorbent for solid-phase extraction (SPE). The morphology and composition of the pine bark were characterized using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The biosorbent was used for the preparation of wastewater for the determination of phenylbutazone, sulfamethazine, carbendazim, and linuron by high performance liquid chromatography with ultraviolet detection (HPLC-UV). The SPE conditions were optimized with respect to elution solvent, sample volume, and extraction pH. The results showed that developed sorbent provides good repeatability. The relative standard deviation (n = 3), was between 0.3 and 2.2%. The limits of detection (LOD) were between 0.11 and 0.4 µg.L −1 . The developed method was used for determination of the analytes in effluent from a wastewater treatment plant.